English english - Prita Ayu Permatasari; Luisa Febrina Amalo; Rahmat Pangestu; Marfian Dwidima Putra (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Citarum River is one of the strategically valuable rivers in Indonesia, especially on Java Island. Since 2018, the central government has carried out the